Pengembangan Instrumen Penilaian Sikap Jujur Pada Pembelajaran Untuk Siswa SD - muslihudin Muslihudin (Tuladha : Jurnal Pendidikan Dasar, 2022)
This study aims to explain the steps to develop an honest attitude assessment instrument for students at SD N 1 Selokromo and to determine the quality of the development product in the form of this instrument. This research is a research type Research and Development (R&D). Data collection techniques with a Likert scale. The results of the questionnaire obtained from google form in the extensive trial showed that the average score obtained was 51.10, the lowest score was 34, the highest was 64. The questionnaire variance was 40.725 while the standard deviation was 6.382. The KMO Measure of Sampling Adequacy (MSA) figure is 0.749. Since the value is (0.749 > 0.5) this indicates the adequacy of the sample. The KMO and Bartlett's Test numbers that appear on the chi-square value are 186,198 with a significance value of 0,000. This shows that there is a correlation between variables, and it is appropriate for further processing. The validity test shows that of the 16 items instruments 13 items are valid. In testing the reliability of the final instrument. To calculate instrument reliability by looking at Cronbach's alpha price> 0.60. With the help of a computer using SPSS version.26, the final instrument was obtained with an alpha coefficient of 0.706. So, it can be concluded that the final instrument items of the study are reliable. A valid and reliable honest attitude assessment instrument for elementary / equivalent students can be used as an assessment guide.